PENGARUH PEMBERIAN DOLOMIT DAN PEMUPUKAN NPK TERHADAP PERTUMBUHAN DAN HASIL OKRA (Abelmoschus esculentus L.) PADA TANAH HISTOSOL - Iwandikasyah Putra; Jasmi Jasmi (Jurnal Agrotek Lestari, 2020)
Abstract Histosol is an organic soil with a high acidity value (pH 4.5) and low levels of nutrients N, P, and K that is effects to plant growth and yield. This study aims to examine the effect of dolomite and NPK fertilization on the growth and yield of Okra (Abelmoschus esculentus L.) on Histosol soil. This research was conducted in the Experimental Garden of the Faculty of Agriculture, Teuku Umar University, West Aceh. This study used a factorial 4 x 4 randomized block design (RBD) with 3 replications. The factors studied include: 1) Dolomite factor (D) consists of 4 levels, namely: D0= without liming, D1= 22.5 grams/polybag, D2= 45 grams/polybag, D3= 67.5 grams / polybag; 2) NPK fertilizer factor (N) consists of 4 levels, namely: N0= zero NPK fertilizer application, N1= 11.25 gram/polybag, N2 = 18.75 grams/polybag, N3= 26.25 grams/polybag. The results showed that dolomite dose had a very significant effect on plant height, stem diameter and number of leaves of okra plants aged 15, 30, 45 and 60 HST. Very significant effect on the length of the okra fruit aged 73 HST and significant effect on the weight of the fruit age 73 HST, but no significant effect on fruit diameter, number of fruit age and production per hectare (tons) 73 HST. NPK fertilizer has a very significant effect on plant height and stem diameter aged 15, 30, 45 and 60 HST. Very significant effect on fruit length and diameter okra fruit aged 73 HST. Not significant effect on the number of fruits, fruit weight and per hectare production (tons) of okra aged 73 HST. There was no interaction between dolomite and NPK fertilizer from all treatments.Keywords : Histosol, acidity, liming and fertilizing, growth and yield of okra plants